ANALISIS PENENTUAN STANDAR WAKTU DAN BIAYA REPARASI KAPAL FERRY PORTLINK III MENGGUNAKAN METODE ACTIVITY BASED COSTING - Mohamad Refhan Haikal (2022)
Over time, the development of industry in Indonesia has progressed, as well as in the marine transportation industry sector. One of the well-known sea transportation industries is the shipyard industry. This industry has the characteristics of being a labor-intensive, capital-intensive industry, and so is its technology. The increasing number of shipbuilding industries in Indonesia, causing a fairly tight competition that requires every shipbuilding industry to carry out various kinds of innovations. Likewise, in terms of cost innovation, the maintenance and repair activities of the PORTLINK III Ferry at PT. DKB Jakarta Shipyard I still use conventional calculation methods to calculate repair costs. On the other hand, there are advantages that can be achieved by shipyards when using the activity-based costing (ABC) method because each activity carried out can be traced to the amount of cost for each activity carried out. Because the ABC method is well detailed about cost, quality, and time factor. In the maintenance and repair activities of the PORTLINK III Ferry ship, the results obtained are Rp. 3,029,112,829, - while for the ABC method calculations, the results are Rp.4.640.078.758., - there is a difference in costs in the calculation of the costs of the two methods of Rp.1.610.965.929, -. The difference occurred due to delays in the ship's work process, which at the beginning was only 18 days to 27 days. In addition, there is additional work which the conventional method cannot be identified widely, but the ABC method can show the overall cost both for initial costs and additional costs. Key Words: Activity Based Costing, Conventional, Repair, PORTLINK III